Volatiles from green‐lipped mussel as a lead to vespid wasp attractants. (19th December 2013) - Unelius, C. R.; El‐Sayed, A. M.; Twidle, A. M.; Stringer, L. D.; Manning, L. M.; Sullivan, T. E. S.; Brown, R. L.; Noble, A. D. L.
Abstract Vespid wasps (Vespula vulgaris L. and V. germanica Fab. Hymenoptera; Vespidae) are highly abundant in 1 million ha of New Zealand's indigenous beech forests (Nothofagus spp.) and have had detrimental effects on the New Zealand native fauna. This hyperabundance is due in part to the vast supply of carbohydrate‐rich honeydew produced by scale insects Ultracoelostoma spp. native to New Zealand. Current control methods include the use of wet cat food as a protein source with insecticide as a lure‐and‐kill‐based system, but there are problems with fresh baits degrading rapidly, and a more durable formulation would enable the expansion and longevity of wasp control. Four crude protein baits were tested for vespid attraction. Green‐lipped mussels had the highest vespid catch of the crude baits tested, and aged and fresh mussels were equally attractive. From headspace analysis of the green‐lipped mussel volatiles, a series of butanoate esters, 3‐octanone and 1‐octen‐3‐ol were identified as possible attractants. These compounds were tested individually and in various blend combinations for the attraction of Vespula wasps in matagouri vegetation at the edge of beech forests. We found synergistic effects between single attractive compounds when tested in various combinations, and the multicomponent lures were more attractive to these wasps than heptyl and octyl butanoate, previously identified attractants for vespid species. The new multicomponent lures could form the basis for a new generation of attractants for social wasps that can provide sustained control methods for invasive vespid wasps.